2017
DOI: 10.1155/2017/1917291
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating IGFBP1 Level with the Severity of Coronary Artery Lesions in Patients with Unstable Angina

Abstract: Aims. Local IGFBP1 level was reported to affect the development of coronary artery plaque. This study investigated the association of circulating IGFBP1 level with the severity of coronary artery lesions in patients with unstable angina. Materials and Methods. In 112 consecutive patients with clinically diagnosed unstable angina, admitted from July 2014 to July 2015, we studied the correlations of circulating IGFBP1 and the severity of coronary artery disease (CAD). Results. All patients underwent scheduled co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…When combined with HDL values, the sensitivity was 0.82. The phosphorylation status was not determined (Zheng et al 2017). Similarly, high IGFBP1 predicted increased risk of mortality in elderly women with the hazard ratio of 3/1 when compared to low IGFBP1 values (Maggio et al 2013).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…When combined with HDL values, the sensitivity was 0.82. The phosphorylation status was not determined (Zheng et al 2017). Similarly, high IGFBP1 predicted increased risk of mortality in elderly women with the hazard ratio of 3/1 when compared to low IGFBP1 values (Maggio et al 2013).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…One new finding emerging from our study utilizing a modern metabolomics approach is that there was an inverse correlation between the level of phIGFBP-1 and several HDL-related particles, which were independent of the serum level of insulin and prepregnancy BMI. In previous studies in non-pregnant study groups, the level of IGFBP-1 has been found to correlate with traditionally measured serum total HDL cholesterol in ischaemic heart disease, type 2 diabetic patients and healthy subjects [ 25 , 26 , 27 ] and in patients with unstable angina [ 28 ]. The inverse relationship between phIGFBP-1 and HDL–particles in our study may be related to the physiological alterations in lipid metabolism associated with pregnancy: typically an increase in the amounts of lipids, particularly in triglycerides and total cholesterol has been reported over the course of pregnancy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, higher IGFBP-1 concentrations were informative for mortality in subjects with no history of heart failure after a follow-up of 8 years. Serum IGFBP-1 concentrations were also significantly increased in patients with critical CAD when compared to patients with less severe CAD ( 22 ). In combination with HDL cholesterol, IGFBP-1 serum concentrations were more sensitive and specific for the prediction of CAD ( 22 ).…”
Section: Igfbp-1mentioning
confidence: 98%
“…Serum IGFBP-1 concentrations were also significantly increased in patients with critical CAD when compared to patients with less severe CAD ( 22 ). In combination with HDL cholesterol, IGFBP-1 serum concentrations were more sensitive and specific for the prediction of CAD ( 22 ). Lower IGFBP-1 and IGF-I serum concentrations were associated with an increased risk of IHD later in life or with higher cardiovascular disease mortality in men and women at an age between 51 and 98 years ( 28 ).…”
Section: Igfbp-1mentioning
confidence: 98%
See 1 more Smart Citation